Pengujian validitas konstruk berbagi pengetahuan pada tim proyek DB - Made Novia Indriani (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
The variable or construct of sharing knowledge is a multidimensional construct. The aim of this research is to test the validity and reliability of the indicators forming the knowledge sharing construct by conducting confirmatory factor analysis (CFA). The knowledge sharing construct is measured using 2 (two) dimensions, namely the tacit knowledge sharing dimension and the explicit knowledge sharing dimension, with 14 (fourteen) indicators that are in accordance with theoretical studies. Factors that influence tacit knowledge sharing and explicit knowledge sharing are analyzed based on field data collected from distributing 120 questionnaires to 40 DB projects in several cities in Indonesia. From the outer loading results, it can be seen that all construct indicators are valid where the resulting t-statistics value is > 1.96. Then from the results of the path coefficients, all first order constructs have a significant effect on the second order construct of knowledge sharing where the resulting t-statistics value for all first order constructs is > 1.96. This means that the knowledge sharing instrument developed has good construct validity and has a high internal consistency reliability coefficient.